A mixed aluminum powder and its application in preparing anode foil of aluminum electrolytic capacitor

By adding specific additives and optimizing particle size composition to the aluminum powder of the aluminum electrolytic capacitor anode foil, the problem of insufficient water and pressure resistance of the existing porous electrode foil is solved, and higher water and pressure resistance and specific capacity are achieved.

CN119747646APending Publication Date: 2025-04-04ZHEJIANG HONGLIANG NEW MATERIAL TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411906314.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The existing porous electrode foils still have room for improvement in water and pressure resistance.

Method used

By adding additives such as aluminum hydroxide, suprasite, tetrahydroxyl alumina and aluminum silicate to high-purity aluminum powder, the D50 particle size composition of the aluminum powder is optimized, and the compactness and specific surface area of ​​the sintered foil are improved.

Benefits of technology

The water and pressure resistance performance of the anode foil of the aluminum electrolytic capacitor is significantly improved, and the specific capacity after chemical formation is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119747646A_ABST
    Figure CN119747646A_ABST
Patent Text Reader

Abstract

The invention discloses a mixed aluminum powder and its application in preparing an anode foil of an aluminum electrolytic capacitor. The raw material composition of the mixed aluminum powder includes high-purity aluminum powder and an additive, and the mass ratio of the additive to the high-purity aluminum powder is (0.8-2.4):100; the additive includes at least one of aluminum hydroxide, boehmite, pseudo-boehmite, tetrahydroxyaluminate and aluminum silicate. The invention mixes an additive into the high-purity aluminum powder, and the additive is selected from at least one of aluminum hydroxide, boehmite, pseudo-boehmite, tetrahydroxyaluminate and aluminum silicate. The addition of these components makes the aluminum powder more compact after sintering, which is conducive to improving the water resistance and pressure resistance of the sintered foil after formation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of aluminum electrolytic capacitors, and in particular relates to a mixed aluminum powder and an application thereof in preparing an anode foil of an aluminum electrolytic capacitor. Background Art

[0002] As the country and society pay more and more attention to environmental and ecological protection and the public's environmental awareness is gradually strengthened, the energy-intensive and highly polluting corrosion foil process is gradually being replaced by the environmentally friendly and energy-saving coated sintered foil. More and more corrosion foil companies have begun to independently develop coated sintered foil processes and undergo transformation.

[0003] For example, a Chinese invention patent with publication number CN114523112B discloses a process for preparing a porous electrode foil, which comprises the following steps: (1) mixing aluminum powder, valve metal oxide powder, a binder and a solvent according to a preset mass percentage to obtain a mixed fluid; (2) coating the mixed fluid on at least one side of an aluminum foil substrate, drying and compacting the mixed fluid to obtain a composite aluminum foil; (3) subjecting the composite aluminum foil to a staged sintering treatment, and subjecting the sintered foil to anodizing treatment to obtain a porous electrode foil.

[0004] Although the porous electrode foil has good specific volume, its water resistance and pressure resistance still need to be improved. Summary of the invention

[0005] The purpose of the present invention is to provide a mixed aluminum powder and its application in the preparation of aluminum electrolytic capacitor anode foil, so as to provide a new and effective way to improve the water resistance and pressure resistance of aluminum electrolytic capacitor anode foil.

[0006] To achieve the above-mentioned object of the invention, the technical solution of the present invention is as follows:

[0007] The present invention first provides a mixed aluminum powder, wherein the raw material composition of the mixed aluminum powder includes high-purity aluminum powder and an additive, and the mass ratio of the additive to the high-purity aluminum powder is (0.8-2.4):100;

[0008] The additive comprises at least one of aluminum hydroxide, boehmite, pseudo-boehmite, tetrahydroxyaluminate and aluminum silicate.

[0009] The present invention mixes an additive into high-purity aluminum powder, and the additive is selected from at least one of aluminum hydroxide, boehmite, pseudo-boehmite, tetrahydroxyaluminate and aluminum silicate. The addition of these components will make the aluminum powder more compact after sintering, which is beneficial to improving the water resistance and pressure resistance of the sintered foil after formation.

[0010] In the present invention, the above-mentioned additives have three adding schemes:

[0011] First, the additive includes at least one of aluminum hydroxide, boehmite, pseudo-boehmite and aluminum silicate, and the mass ratio of the additive to the high-purity aluminum powder is (0.8-1.3):100;

[0012] The purity of the aluminum hydroxide, boehmite or aluminum silicate is not less than 99.99%, and the D50 particle size is between 1-1.5 μm;

[0013] Second, the additive is tetrahydroxyaluminate with a purity of not less than 99.99%, and the mass ratio of the additive to the high-purity aluminum powder is (1.1-2.4):100;

[0014] Third, the additive is composed of the following two components:

[0015] ① The mass ratio of at least one of aluminum hydroxide, boehmite, pseudo-boehmite and aluminum silicate to high-purity aluminum powder is (0.3-0.5):100;

[0016] ② The mass ratio of tetrahydroxyaluminate to high-purity aluminum powder is (0.5-0.8):100.

[0017] The first and second schemes can give the anode foil basically equivalent water resistance and pressure resistance, while the third scheme can give the anode foil better water resistance and pressure resistance.

[0018] Preferably, in the above-mentioned mixed aluminum powder, the purity of the high-purity aluminum powder is not less than 99.99%;

[0019] Measured by mass percentage, the high-purity aluminum powder is composed of the following four types of aluminum powders with different D50 particle sizes: 15%-22% of aluminum powder with a D50 particle size of 0.35-0.5μm, 40%-48% of aluminum powder with a D50 particle size of 1.5-3.5μm, 30%-43% of aluminum powder with a D50 particle size of 5-6.5μm, and 5%-10% of aluminum powder with a D50 particle size of 8-10μm.

[0020] The present invention optimizes the D50 particle size composition of high-purity aluminum powder. By controlling the proportion of various D50 particle size aluminum powders in the aluminum powder, the aluminum powder particles can be stacked more closely without increasing the coating thickness, thereby achieving effective connection and forming a conductive channel, further reducing the presence of waste particles, and increasing the specific surface area of ​​the sintered foil, thereby greatly improving the water and pressure resistance of the anode foil, and the specific volume after formation is also significantly improved.

[0021] The present invention also provides a preparation process of the mixed aluminum powder, which comprises: mixing high-purity aluminum powder and additives in an inert protective atmosphere and sealing and storing them.

[0022] Preferably, in the above-mentioned preparation process, the temperature inside the chamber is controlled between 15-25° C. during the mixing process. The purpose is to ensure that the temperature inside the chamber during the aluminum powder mixing process is in a safe environment and reduce safety risks.

[0023] The present invention also provides the use of the mixed aluminum powder in preparing an anode foil of an aluminum electrolytic capacitor; and an anode foil of an aluminum electrolytic capacitor, wherein the anode foil is prepared by the following method:

[0024] (1) mixing the above-mentioned mixed aluminum powder with water to obtain aluminum powder slurry;

[0025] (2) coating the aluminum powder slurry on an aluminum foil substrate to obtain a coated foil;

[0026] (3) sintering the coated foil under an inert atmosphere to obtain a sintered foil;

[0027] (4) The sintered foil is subjected to chemical formation to obtain the aluminum electrolytic capacitor anode foil.

[0028] Compared with the prior art, the technical effects of the present invention are embodied in:

[0029] (1) The present invention mixes an additive into the high-purity aluminum powder. The additive is selected from at least one of aluminum hydroxide, boehmite, pseudo-boehmite, tetrahydroxyaluminate and aluminum silicate. The addition of these ingredients makes the aluminum powder more compact after sintering, which is beneficial to improving the water resistance and pressure resistance of the sintered foil after formation.

[0030] (2) The present invention optimizes the D50 particle size composition of high-purity aluminum powder. By controlling the proportion of various D50 particle size aluminum powders in the aluminum powder, the aluminum powder particles can be stacked more closely without increasing the coating thickness, thereby achieving effective connection and forming a conductive channel, further reducing the presence of waste particles, and increasing the specific surface area of ​​the sintered foil, thereby greatly improving the water and pressure resistance of the anode foil, and the specific volume after formation is also significantly improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 These are electron microscope observation images of the plane and cross section of sintered foils made with different aluminum powders. DETAILED DESCRIPTION

[0032] The technical solution of the present invention is further described in detail below in conjunction with the accompanying drawings and specific implementation methods.

[0033] Examples 1-5

[0034] The present embodiment provides a mixed aluminum powder, and the preparation process thereof includes:

[0035] (a) selecting high-purity aluminum powder with a D50 particle size of 5.0 μm, which is produced by a professional aluminum powder production enterprise and has a purity of not less than 99.99%;

[0036] (b) selecting four additives, namely, aluminum hydroxide, boehmite, tetrahydroxyaluminate, and aluminum silicate, and mixing them with the high-purity aluminum powder to obtain a mixed aluminum powder;

[0037] The mixing process is carried out in a special aluminum powder mixing machine under an inert protective atmosphere (argon, nitrogen or neon). The mixing chamber must be equipped with a cooling cycle. The temperature of the mixing chamber is controlled between 15-25°C during the mixing process. After the mixing is completed, the mixed aluminum powder is bagged and sealed for storage.

[0038] At the same time, the same aluminum powder was taken without adding additives as a comparison.

[0039] The type, purity, D50 particle size and addition ratio of each additive are shown in Table 1.

[0040] Table 1

[0041]

[0042] Example 6

[0043] The present embodiment provides a mixed aluminum powder, and the preparation process thereof includes:

[0044] (a) selecting high-purity aluminum powders with D50 particle sizes of 0.5 μm, 3.0 μm, 6.0 μm, and 9.0 μm, respectively, the high-purity aluminum powders are produced by a professional aluminum powder production enterprise, and the purity is not less than 99.99%;

[0045] (b) The four aluminum powders were mixed according to the mass ratio in Table 2 (the mixing method was the same as in Examples 1-5) to obtain 500 g of mixed aluminum powder (Sample 6).

[0046] Table 2

[0047] Aluminum powder D50 particle size Proportion 0.5μm 15% 3.0μm 45% 6.0μm 35% 9.0μm 5%

[0048] Similarly, high-purity aluminum powders with two sizes of D50 particle size of 2.5 μm and 9.0 μm were selected as comparisons (CK comparison sample 2 and CK comparison sample 3).

[0049] Example 7

[0050] The present embodiment provides a mixed aluminum powder, and the preparation process thereof includes:

[0051] (a) selecting high-purity aluminum powders with D50 particle sizes of 0.35 μm, 3.5 μm, 5.0 μm, and 10.0 μm, respectively, the high-purity aluminum powders are produced by a professional aluminum powder production enterprise, and the purity is not less than 99.99%;

[0052] (b) The four aluminum powders were mixed in the mass ratio shown in Table 3 (the mixing method was the same as in Examples 1-5) to obtain 500 g of mixed aluminum powder (Sample 7).

[0053] Table 3

[0054] Aluminum powder D50 particle size Proportion 0.35μm 10% 3.5μm 45% 5.0μm 37% 10.0μm 8%

[0055] Similarly, high-purity aluminum powders with two sizes of D50 particle size of 3.0 μm and 10.0 μm were selected as comparisons (CK comparison sample 4 and CK comparison sample 5).

[0056] Example 8

[0057] The present embodiment provides a mixed aluminum powder, and the preparation process thereof includes:

[0058] (a) Aluminum powders with D50 particle sizes of 0.5 μm, 3.0 μm, 6.0 μm, and 9.0 μm were selected. The high-purity aluminum powders were produced by a professional aluminum powder production enterprise, and the purity was not less than 99.99%;

[0059] (b) The four aluminum powders were mixed according to the mass ratio of Table 3 to obtain 500 g of mixed high-purity aluminum powder;

[0060] (c) Tetrahydroxyaluminic acid and aluminum silicate (purity and particle size see Table 1) are selected as additives and mixed with the above-mentioned mixed high-purity aluminum powder (the mixing method is the same as that of Examples 1-5) to obtain mixed aluminum powder.

[0061] At the same time, aluminum powder with a D50 particle size of 5.0 μm (CK comparison sample 6), the mixed high-purity aluminum powder of step (b) (CK comparison sample 7) and CK comparison sample 8 were used as comparisons.

[0062] The type, purity, D50 particle size and addition ratio of each additive are shown in Table 4.

[0063] Table 4

[0064]

[0065] Examples 9-16

[0066] The present embodiment provides an aluminum electrolytic capacitor anode foil, and its preparation process includes the following steps:

[0067] (1) The mixed aluminum powders prepared in the above Examples 1-8 and the corresponding comparative examples were mixed with water at a mass ratio of 2:3 to obtain aluminum powder slurry;

[0068] (2) coating the aluminum powder slurry on an aluminum foil substrate to obtain a coated foil;

[0069] Specifically, each aluminum powder slurry was coated on an aluminum foil substrate with a thickness of 30 μm using a laboratory automatic coating machine, and the single-side coating thickness was 50 μm. After the single-side coating was completed, it was dried and then coated on the other side to obtain a coated foil;

[0070] (3) sintering the coated foil under an inert atmosphere to obtain a sintered foil;

[0071] Specifically, each coated foil was placed in a tubular furnace for thermal sintering, and nitrogen was introduced at a flow rate of 250 mL / min during the sintering process; the sintering temperature was 610° C., and the sintering time was 8 h; after the sintering was completed, a sintered foil was obtained;

[0072] (4) performing laboratory chemical formation on the sintered foil to obtain the aluminum electrolytic capacitor anode foil of this embodiment;

[0073] The formation steps are as follows:

[0074] ① Hydration: First, wash the foil with pure water, and then boil it in 95℃ pure water for 5-10 minutes;

[0075] ②Electrification: Fix the cleaned foil on the flat iron bar with an alligator clip and place it on the small sample slot rack. Set the corresponding time and voltage parameters, perform one-time electrochemical reaction, and press the "Start" button to start the electrochemical process. After the electrochemical operation is completed, remove the foil, wash it with pure water, record the power value, and proceed to the next process.

[0076] The formation sequence is as follows: F1→F2→F3 / 4→F5→muffle furnace 520℃2min→F5a→soak in phosphoric acid (70℃, 5min) and then rinse with pure water→F5a→muffle furnace 520℃2min→F5a→soak in diammonium phosphate (66.3℃, 2min) and then rinse with pure water;

[0077] The time and voltage parameters of F1-F5a are shown in Table 5 below;

[0078] Table 5

[0079] Forming tank F1 F2 F3 / 4 F5 F5a Time / s 450 320 520 720 420 Voltage / V 180 360 480 515 515 Temperature / ℃ 85 85 85 85 85

[0080] ③ Time and voltage test: After drying the formed foil in step ②, use a punching machine to make a bow-shaped foil and place it on the equipment. Open the computer software, set the charging current to 3.00mA, the withstand voltage to 515.0V, the TV delay to 120s, the leakage voltage to 465V, and the leakage delay to 240s. Click "Start Test" to start; wait for the instrument test results and record them; after the test is over, wash the foil with pure water for later use;

[0081] ④Test the electrostatic capacitance of the foil.

[0082] The performance test results of each anode foil are shown in Table 6.

[0083] Table 6

[0084]

[0085] It can be seen from Table 6 that compared with CK comparison sample 1, under the condition of the same anode foil thickness, due to the addition of additives in samples 1-5, the Tv (reaching voltage) value of the anode foil obtained is closer to the set voltage, and the Tr (rise time) value and Tr60 value are smaller; in particular, the reaching voltage of samples 3 and 5 is basically equivalent to the set voltage, and the rise time is shorter, indicating that the anode foil has better conduction performance and excellent voltage resistance; the Tr60 value is lower, indicating that the anode foil has excellent water resistance; the specific volume is also improved; sample 5 has better performance of the anode foil due to the addition of aluminum silicate and tetrahydroxyaluminic acid, indicating that the combination of the two additives has a synergistic effect, and the total amount of additives used is reduced.

[0086] Compared with CK comparison samples 2 and 3, sample 6 has better performance; compared with CK comparison samples 4 and 5, sample 7 has better performance; this shows that the organic combination of high-purity aluminum powder with multiple particle sizes can also achieve the same technical effect as additives.

[0087] At the same magnification, the plane and cross section of the sintered foils made of CK comparative sample 2, CK comparative sample 3 and sample 6 were observed by electron microscope. The results are as follows: Figure 1 As shown in the cross-sectional diagram, it can be seen that the cross-sectional particles of the sintered foil made from CK comparative sample 2 are densely stacked with almost no gaps; the cross-sectional particles of the sintered foil made from CK comparative sample 3 have many gaps; and in sample 6, due to the addition of 0.5μm small-particle aluminum powder, some of the gaps are filled, promoting the sintering and connection between particles and forming a conductive path; this may be the reason why the anode foil made from mixed high-purity aluminum powder with a combination of multiple particle sizes has better performance.

[0088] It can be seen from samples 8, 9 and 10 that when the mixed aluminum powder not only adds additives but also optimizes the particle size ratio of high-purity aluminum powder, the various properties of the anode foil are better than those when the additives are added alone or the particle size ratio of high-purity aluminum powder is optimized alone.

Claims

1. A mixed aluminum powder, characterized in that: The raw material composition includes high-purity aluminum powder and additives, and the mass ratio of the additive to the high-purity aluminum powder is (0.8-2.4):100; The additive comprises at least one of aluminum hydroxide, boehmite, pseudo-boehmite, tetrahydroxyaluminate and aluminum silicate.

2. The mixed aluminum powder according to claim 1, characterized in that The additive comprises at least one of aluminum hydroxide, boehmite, pseudo-boehmite and aluminum silicate, and the mass ratio of the additive to the high-purity aluminum powder is (0.8-1.3):

100.

3. The mixed aluminum powder according to claim 2, characterized in that: The purity of the aluminum hydroxide, boehmite or aluminum silicate is not less than 99.99%, and the D50 particle size is between 1-1.5 μm.

4. The mixed aluminum powder according to claim 1, characterized in that The additive is tetrahydroxyaluminate with a purity of not less than 99.99%, and the mass ratio of the additive to the high-purity aluminum powder is (1.1-2.4):

100.

5. The mixed aluminum powder according to claim 4, characterized in that: The additive is composed of the following two components: ① The mass ratio of at least one of aluminum hydroxide, boehmite, pseudo-boehmite and aluminum silicate to high-purity aluminum powder is (0.3-0.5):100; ②Tetrahydroxyaluminic acid, the addition amount is at a mass ratio of (0.5-0.8) to high-purity aluminum powder:

100.

6. The mixed aluminum powder according to claim 1, characterized in that The purity of the high-purity aluminum powder is not less than 99.99%; Measured by mass percentage, the high-purity aluminum powder is composed of the following four types of aluminum powders with different D50 particle sizes: 15%-22% of aluminum powder with a D50 particle size of 0.35-0.5μm, 40%-48% of aluminum powder with a D50 particle size of 1.5-3.5μm, 30%-43% of aluminum powder with a D50 particle size of 5-6.5μm, and 5%-10% of aluminum powder with a D50 particle size of 8-10μm.

7. The process for preparing the mixed aluminum powder according to any one of claims 1 to 6, characterized in that: include: Under an inert protective atmosphere, high-purity aluminum powder and additives are mixed and sealed for storage.

8. The preparation process according to claim 7, characterized in that: During the mixing process, circulating cooling is required to control the temperature inside the cabin between 5-25°C.

9. Use of the mixed aluminum powder as claimed in any one of claims 1 to 6 in preparing anode foil of aluminum electrolytic capacitors.

10. An aluminum electrolytic capacitor anode foil, characterized in that: Made by the following method: (1) mixing the mixed aluminum powder as described in any one of claims 1 to 6 with water to obtain an aluminum powder slurry; (2) coating the aluminum powder slurry on an aluminum foil substrate to obtain a coated foil; (3) sintering the coated foil under an inert atmosphere to obtain a sintered foil; (4) The sintered foil is subjected to chemical formation to obtain the aluminum electrolytic capacitor anode foil.

Citation Information

Patent Citations

  • A porous electrode foil and its preparation process

    CN114523112B